2017
DOI: 10.1364/oe.25.007349
|View full text |Cite
|
Sign up to set email alerts
|

Fast axial-scanning photoacoustic microscopy using tunable acoustic gradient lens

Abstract: An optical-resolution photoacoustic microscope (OR-PAM) with capability of fast axial-scanning was developed by using a tunable acoustic gradient (TAG) lens. The TAG lens was designed to continuously changing the focal plane of OR-PAM by modulating its refractive power with fast-changing ultrasonic standing wave. The performance was shown by imaging a carbon fiber. We achieved a DoF of about 750 μm. The head of a zebrafish was also imaged to further demonstrate the feasibility of our method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…This can be implemented using the geometry of dual-beam illumination on a fast-scanning imaging head or by applying a tunable acoustic gradient lens. 32 Moreover, the degradation of lateral resolution due to optical scattering may be partially mitigated within a certain depth range by implementing PAM with adaptive optics. 33 DAI-PAM could also benefit quantitative multiwavelength PAM for measuring blood oxygenation in the cortex, such as the oxygen saturation in cerebral diving vessels demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This can be implemented using the geometry of dual-beam illumination on a fast-scanning imaging head or by applying a tunable acoustic gradient lens. 32 Moreover, the degradation of lateral resolution due to optical scattering may be partially mitigated within a certain depth range by implementing PAM with adaptive optics. 33 DAI-PAM could also benefit quantitative multiwavelength PAM for measuring blood oxygenation in the cortex, such as the oxygen saturation in cerebral diving vessels demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…When tumor volume of H22 tumor-bearing mice grew up to 100-150 mm 3 , the mice were intratumorally injected with AuNCs or CAuNCs at Au dose of 10 mg/kg. At different time intervals, the mice were scanned on a homemade photoacoustic system to collect the photoacoustic signals 37 , 38 . The wavelength of laser was 744 nm and the laser energy per pulse was 200 nJ.…”
Section: Methodsmentioning
confidence: 99%
“…The TAG lens is an adaptive lens that can change its effective focal length in a few microseconds or less [64], so it has been widely used for varifocal imaging [[65], [66], [67]]. Yang et al in 2017 reported an OR-PAM system using a TAG lens to extend the DoF [68]. The TAG lens consisted of a cylindrical piezoelectric shell filled with silicone oil and its focal length can be shifted according to the applied sinusoidal signal.…”
Section: Image Enhancement In Out-of-focus Regionsmentioning
confidence: 99%